LANGUAGE EXPRESSION, SENSE, AND DENOTATUM CONSTRUCTED FROM GO’ET IN MANGGARAI LANGUAGE - Daar, Gabriel Fredi; Beratha, Ni Luh Sutjiati; Beratha, Ni Luh Sutjiati (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 32 No 1 (2025): MaretDO - 10.24843/ling.2025.v32.i01.p06, 2025)
This study aims to describe the language expressions, sense, and denotatum that exist in the go'et of the Manggarai language. Data related to go'et of the Manggarai language were obtained through interviews with five Manggarai elders who had sufficient knowledge of the Manggarai language and culture. There are three data of advice go'et used as material for analysis. This study provided some insights related to semantic studies. First, the relationship of language expressions, sense and denotatum can be found in certain language that is recently rare studied. As it is identified in the go’et of Manggarai language, the relationship can happen in certain context of language use. For instance, go’et is only used in cultural activities, and is usually spoken by the elders who have cultural knowledge and good Manggarai language skills. Second, the use of qualitative study provides some understanding of semantic meaning of g o'et . It has a sense and denotatum that can be interpreted through certain mental actions which is related to social life of the Manggarai community.